Physics conclusions in support of ITER W divertor monoblock shaping. (August 2017) - Pitts, R.A.; Bardin, S.; Bazylev, B.; van den Berg, M.A.; Bunting, P.; Carpentier-Chouchana, S.; Coenen, J.W.; Corre, Y.; Dejarnac, R.; Escourbiac, F.; Gaspar, J.; Gunn, J.P.; et al.
Highlights: Focus is on protection of leading edges between toroidally adjacent monoblocks. Summarizes conclusions of coordinated, multi-device ITPA Divertor and SOL task. Leading loading found to be well described by optical approximation. Shaping required to prevent deep edge melting during steady state and ELMs. Shaping implies reduced parallel heat flux to avoid material crystallization. Abstract: The key remaining physics design issue for the ITER tungsten (W) divertor is the question of monoblock (MB) front surface shaping in the high heat flux target areas of the actively cooled targets. Engineering tolerance specifications impose a challenging maximum radial step between toroidally adjacent MBs of 0.3 mm. Assuming optical projection of the parallel heat loads, magnetic shadowing of these edges is required if quasi-steady state melting is to be avoided under certain conditions during burning plasma operation and transiently during edge localized mode (ELM) or disruption induced power loading. An experiment on JET in 2013 designed to investigate the consequences of transient W edge melting on ITER, found significant deficits in the edge power loads expected on the basis of simple geometric arguments, throwing doubt on the understanding of edge loading at glancing field line angles. As a result, a coordinated multi-experiment and simulation effort was initiated via the International Tokamak Physics Activity (ITPA) and through ITER contracts, aimed at improving the physics basis supporting a MB shaping decision from the point of view both of edge power loading and melt dynamics. This paper reports on the outcome of this activity, concluding first that the geometrical approximation for leading edge power loading on radially misaligned poloidal leading edges is indeed valid. On this basis, the behaviour of shaped and unshaped monoblock surfaces under stationary and transient loads, with and without melting, is compared in order to examine the consequences of melting, or power overload in context of the benefit, or not, of shaping. The paper concludes that MB top surface shaping is recommended to shadow poloidal gap edges in the high heat flux areas of the ITER divertor targets.